The Story of a Spirit: Narrativity and Temporality in Descartes’s Discourse on the Method - Sousa, Frederico Duarte Pires de (Cadernos Espinosanos, 2020)
This paper intends to redeem, even modestly, the temporality and the narrativity present in the Discourse on the Method (1637), and thus, to situate them in relation to the Cartesian project of legitimizing its conception of science and philosophy – step that marks his metaphysical turn given the condemnation of Galileo in 1633. Complementing and deepening this key of reading of the small essay of Descartes, we will trace a brief analysis of the philosophical meaning of the figure of the Journey – present in an important way in the body of the text. In this spirit, our proposal is to understand how the aesthetic dimension of this Descartes’s work dialogues with its philosophical dimension.